Can Cervical Cerclage Prevent Umbilical Cord Prolapse in Patients with Funic Presentation?. (March 2021) - Petrikovsky, B.; Terrani, M.; Dillon, A.; Sichinava, L.
Objective: Umbilical cord prolapse is a rare event complicating 0.17%–0.62% of all pregnancies. Funic presentation is a known risk factor for umbilical cord prolapse. Currently, there is no strategy to prevent umbilical cord prolapse in patients with funic presentation. The novel technique used is placement of late cervical cerclage to create a mechanical barrier and prevent an umbilical cord prolapse. Methods: Six patients with a sonographically detected funic presentation were included in the study. Funic presentation was defined as the sonographic presence of the umbilical cord below the presenting part using both transabdominal and transvaginal sonography. Cord prolapse was defined as an umbilical cord seen or palpated below the presenting part. Cervical cerclage was placed in patients with persistent funic presentations, which is the detection of the umbilical cord below the presenting part, on two or more sonograms at least a week apart. Results: Cervical cerclages were placed in six patients with funic presentation between 28 and 34 weeks of gestation without immediate complications. All patients were delivered by a cesarean section between 35 and 38 weeks of pregnancy. None experienced umbilical cord prolapse. Funic presentation was confirmed at birth in all cases. Apgar scores varied between 7 and 10. Conclusion: It appears that cervical cerclage may be an effective measure to prevent umbilical cord prolapse in cases of known persistent funic presentation.